Thermomechanical optimization of primary cooling systems in the continuous steel slab casting process - Pourfathi, Ali (Thermal science and engineering progress, 2025)
The objectives are determining the mold’s optimal technical parameters to avoid breakout, finding the air gap’s thermal distributions and heat transfer coefficient, and demonstrating the modes and distribution of stresses that the solid shell bears. For this purpose, a new methodology is proposed, which solves two optimization problems individually and respectively. The first optimization problem aims to find the optimal distributions of the air gap’s heat transfer coefficient and temperature to produce a sound solidified shell at the mold exit. In this regard, constraints such as breakout(at least %10 of the whole slab thickness at the mold exit) and temperature-dependent critical tensile strength (CTS) are imposed on the objective function constructed based on the solidified shell’s elastic strain and thermal energies. The distributions of the air gap’s heat transfer coefficient and temperature are employed in the second optimization problem. The aim of the second optimization problem is to determine the mold’s working parameters, such as the cooling water inlet and outlet temperatures and the water flow rate inside the mold’s channels, through a thermal optimum design strategy. The objective function is based on the minimum thermal resistances of the mold’s wall and air gap. The thermophysical proprieties are calculated directly with respect to temperature using computational thermodynamics software packages for the first optimization problem. Furthermore, both problems are solved numerically using a finite elements method and a projected steepest descent algorithm. The success of this methodology is examined using an experimental test for the continuous casting of a commercial low-carbon steel grade. Using the CTS and the numerical thermal distribution obtained from the solid shell, the maximum values of stresses that the shell bears along the thickness, casting, width, and Von-mises equal to 0.07MPa, 0.18MPa, 0.09MPa, and 0.095MPa, each of which is far less than their corresponding CTSs (between 2.7MPa to 10.31MPa). In addition, the calculated mold’s parameters, including 0.1m3s the water flow rate and 12 °C inlet-outlet temperature difference of water, indicate mold’s maximum cooling capability to prevent breakout. The computed and measured temperatures of the mold’s narrow face are compared, and their relative errors have been about 1.1%, 0.6%, 2.35%, 1.1%, 2.3%, 2.1%, 2.5%. The average is 2%, which is small enough to confirm the admissibility of the proposed methodology. •For the first time, a new design methodology was used to determine the working parameters of the primary cooling systems in the continuous casting process.•Coupling mechanical and heat transfer PDEs to find the distribution of the temperature of the air gap and to determine the heat transfer coefficient of the air gap.•Finding the optimal thermal distribution on the copper plate of the primary cooling system.•Comparing the plant values with calculated values in the model to study the design methodology’s performance. [Display omitted]